Phonological specificity in children at 1;2. - Ballem, K; Plunkett, K (2005)
The specificity of infants' phonological representations is examined by comparing their sensitivity to mispronunciations of novel and familiar words, using the preferential looking task. 29 children at 1; 2 were trained and tested on familiar and novel word-object pairs. Children showed evidence of sensitivity to mispronunciations of novel and familiar words, indicating detailed phonological representations. Discrepancies between this study and earlier investigations are discussed with reference to differences between habituation and preferential looking tasks.